Electrophysiological Predictors of Clinical Outcome in Traumatic Neuropathies: A Multicenter Prospective Study. (28th July 2016) - Ciaramitaro, Palma; Mondelli, Mauro; Rota, Eugenia; Battiston, Bruno; Sard, Arman; Pontini, Italo; Faccani, Giuliano; Migliaretti, Giuseppe; Merola, Aristide; Cocito, Dario; Neuropathies, Italian Network for Traumatic
Abstract : Objectives . This prospective, observational, multicentre study aims to identify electrodiagnostic (EDX) markers of clinical recovery in patients with traumatic neuropathy (TN) receiving surgical (S) and nonsurgical (NS) treatments. Methods . Subjects referred to the Italian Traumatic Neuropathy Network between 2010 and 2011 (307 patients, for a total of 444 TN) were evaluated with serial clinical/EDX evaluations at 6, 12, 24, and 36 months of follow-up. Results . Primary surgery was performed in 21 subjects with open lesions and evidence of neurotmesis, while closed lesions were treated with either conservative medical approach (216 patients) or secondary surgery (70 patients), according to the clinical spontaneous recovery at 4–6 months. Clinical improvement correlated with the increase of the compound muscle action potential amplitude (OR 3.76; CI 1.61–8.76), particularly in the S group (OR 7.25; CI 1.2–43.87), and with sensory nerve action potential amplitude in the NS group (OR 4.35; CI 1.14–16.69). No correlations were found with needle electromyography qualitative evaluations, changes in maximal voluntary recruitment, age, and gender. Conclusions . Nerve conduction studies (NCS) represent the more accurate neurophysiological markers of clinical outcome in patients with TN. Significance . Serial NCS assessments predict the functional recovery in TN, increasing the accuracy of peripheral nerves surgical decision-making process.